Bovine placenta: A review on morphology, components, and defects from terminology and clinical perspectives - Peter, Augustine T. (Theriogenology, 2013)
The bovine placenta has been the subject of many studies. Concurrently, several specialized terms have been developed to describe its development, morphology, components, function, and pathology. Many of these terms are simple, some are difficult to understand and use, and others are antiquated and may not be scientifically accurate. Defining and adopting terminology for the bovine placenta that is clear, precise and understandable, and available in a single source is expected to facilitate exchange of clinical and research information. This review presents a brief overview of the current knowledge regarding the bovine placenta and attempts to define terms. In this process, conventional terminology is presented, and contemporary and novel terms are proposed from a biological perspective. For example, use of terms such as syndesmochorial, retained placenta, and large offspring syndrome should be revisited. Furthermore, the clinical relevance of the structure and function of the bovine placenta is reviewed. Finally, terms discussed in this review are summarized (in table format).